Cervical Anterolisthesis: A Predictor of Poor Neurological Outcomes in Cervical Spondylotic Myelopathy Patients After Cervical Laminoplasty. Issue 8 (April 2016) - Oichi, Takeshi; Oshima, Yasushi; Taniguchi, Yuki; Matsubayashi, Yoshitaka; Chikuda, Hirotaka; Takeshita, Katsushi; Tanaka, Sakae
Abstract : Study Design: A retrospective cohort study. Objective: To clarify the influence of cervical spondylolisthesis on neurological outcomes in cervical spondylotic myelopathy (CSM) patients after cervical laminoplasty. Summary of Background Data: Studies focusing on the surgical outcomes in CSM patients with cervical spondylolisthesis are limited. Methods: We retrospectively reviewed 125 CSM patients after cervical laminoplasty. Neurological outcomes were evaluated by calculating the Japanese Orthopedic Association (JOA) recovery rate at 2 years after surgery. We defined anterolisthesis as a more than 3-mm anterior vertebral displacement in a flexion radiograph and retrolisthesis as a more than 3-mm posterior vertebral displacement in an extension radiograph. We further assessed potential risk factors for poor neurological outcomes after cervical laminoplasty, including cervical alignment, degree of spinal cord compression, duration of myelopathic symptoms, diabetes mellitus, and preoperative JOA score. Multivariate logistic regression analysis was performed to investigate the risk factors for poor outcomes (JOA recovery rate <50%) after cervical laminoplasty. Results: Our study included 86 men and 39 women with mean age of 64 (range, 30–89) years. Average JOA scores were 9.9 and 13.3 points before and at 2 years after surgery, respectively. Average recovery rate was 47.2% (range, −68% to 100%), with 62 patients having poor outcomes (JOA recovery rate <50%) at 2 years after surgery. Anterolisthesis and retrolisthesis were observed in 13 and 24 patients, respectively. Multivariate logistic regression analysis revealed that the anterolisthesis was a significant risk factor for poor outcomes (JOA recovery rate <50%) after cervical laminoplasty ( P = 0.01), whereas retrolisthesis did not affect the neurological outcomes ( P = 0.6). Conclusion: Anterolisthesis, but not retrolisthesis, is a significant risk factor for and predictor of poor neurological outcomes after cervical laminoplasty. Cervical laminoplasty should not be considered in CSM patients with anterolisthesis. Level of Evidence: 2